COMBINED LIVER-PANCREAS TRANSPLANTATION: THE FIRST RUSSIAN EXPERIENCE - S. V. Gautier; O. M. Tsirulnikova; V. N. Poptsov; S. V. Arzumanov; I. V. Pogrebnichenko; A. A. Ammosov; Y. E. Lurie; N. S. Muratova; N. V. Gamgiya; H. M. Hizroev; S. V. Fokin; V. V. Pchelnikov (Вестник трансплантологии и искусственных органов)
Combined liver-pancreas transplantation is considered to be a reasonable treatment of patients with end-stage liver disease and concomitant insulin-dependent diabetes mellitus, so it may become a standard treatment of this category of patients. As known, diabetes mellitus negatively affects the long-term results of isolated liver transplantation and increases a risk of posttransplant complications. Notwithstanding the widening range of indi- cations for simultaneous liver-pancreas transplantation and advances of transplantology, this operation continues to be a rare event in world medical practice. In May 2010 in Academician V.I. Shumakov Federal Research Cen- ter of Transplantology and Artificial Organs there was performed a first in Russia simultaneous liver-pancreas transplantation to 17-years old recipient, suffering with liver cirrhosis (as a result of autoimmune hepatitis) and concomitant insulin-dependent diabetes mellitus. In this article we give an overview of indications for simultaneous liver-pancreas transplantation, different ope- rative techniques, immunological aspects and immunosuppression regimes, as well as we describe the first in Russian experience of such transplantation.